A comparison of the efficacy of carbetocin and oxytocin on hemorrhage-related changes in women with cesarean deliveries for different indications - Yen-Tin Chen; Szu-Fu Chen; T'sang-T'ang Hsieh; Liang-Ming Lo; Tai-Ho Hung (Elsevier, 2018)
Objective: To compare the efficacy of carbetocin and oxytocin on hemorrhage-related changes in women with cesarean deliveries (CS) for different indications. Materials and methods: A retrospective cohort study was conducted on 1568 women with CS before labor onset (elective CS, n = 1153) or during labor (intrapartum CS, n = 415) after 24 weeks' gestation. We compared the fall in hemoglobin (Hb) and hematocrit (Hct) levels after CS, estimated blood loss, the need for additional uterotonic agents, blood transfusion, and the rate of postpartum hemorrhage between women with carbetocin and women with oxytocin treatment, stratified by indications for CS. Results: For women with elective CS, decreased Hb and Hct falls were noted with carbetocin treatment compared to oxytocin treatment in women with indications for prior CS, fetal malpresentation, and multiple gestation. The need for additional uterotonics was less in CS for prior CS, fetal malpresentation, and cephalopelvic disproportion and fewer transfusions in CS for multiple gestation in women with carbetocin compared to women with oxytocin treatment. For women with intrapartum CS, carbetocin was associated with decreased use of additional uterotonic agents and transfusion in CS for dysfunctional labor. Conclusion: Carbetocin and oxytocin had differential effects on hemorrhage-related changes in women with CS for different indications. Keywords: Carbetocin, Cesarean delivery, Oxytocin, Postpartum hemorrhage